(untitled) (Journal of Medical & Health Sciences Review, 2025)
This short review presents the Lactococcus spp. are gram-positive, facultatively anaerobic bacteria widely recognized for their essential role in dairy fermentation processes, particularly in cheese and yogurt production. Their ability to produce lactic acid and contribute to flavor and texture makes them indispensable in the dairy industry. This review explores the latest advancements in the isolation and identification techniques of Lactococcus spp. from cow milk, highlighting their fermentation potential and biotechnological applications. Furthermore, the article discusses the challenges and future perspectives in enhancing the efficiency and reliability of Lactococcus strains for commercial applications. Our discussion covers various bioactive compounds such as Gamma Amino Butyric Acid (GAMMA), Exopolysaccharides (EPs), Bacteriocins, Conjugated Linoleic acid (CLA), Bioactive peptides, lactic acid and citrate, vitamins and enzymes detailing their composition and potential application.